Optimization of photocrosslinked gelatin/hyaluronic acid hybrid scaffold for the repair of cartilage defect. (19th June 2019) - Lin, Hang; Beck, Angela M.; Shimomura, Kazunori; Sohn, Jihee; Fritch, Madalyn R.; Deng, Yuhao; Kilroy, Evan J.; Tang, Ying; Alexander, Peter G.; Tuan, Rocky S.
Abstract: There is no therapy currently available for fully repairing articular cartilage lesions. Our laboratory has recently developed a visible light‐activatable methacrylated gelatin (mGL) hydrogel, with the potential for cartilage regeneration. In this study, we further optimized mGL scaffolds by supplementing methacrylated hyaluronic acid (mHA), which has been shown to stimulate chondrogenesis via activation of critical cellular signalling pathways. We hypothesized that the introduction of an optimal ratio of mHA would enhance the biological properties of mGL scaffolds and augment chondrogenesis of human bone marrow‐derived mesenchymal stem cells (hBMSCs). To test this hypothesis, hybrid scaffolds consisting of mGL and mHA at different weight ratios were fabricated with hBMSCs encapsulated at 20 × 10 6  cells/ml and maintained in a chondrogenesis‐promoting medium. The chondrogenenic differentiation of hBMSCs, within different scaffolds, was estimated after 8 weeks of culture. Our results showed that mGL/mHA at a 9:1 (%, w/v) ratio resulted in the lowest hBMSC hypertrophy and highest glycosaminoglycan production, with a slightly increased volume of the entire construct. The applicability of this optimally designed mGL/mHA hybrid scaffold for cartilage repair was then examined in vivo. A full‐thickness cylindrical osteochondral defect was surgically created in the rabbit femoral condyle, and a three‐dimensional cell–biomaterial construct was fabricated by in situ photocrosslinking to fully fill the lesion site. The results showed that implantation of the mGL/mHA (9:1) construct resulted in both cartilage and subchondral bone regeneration after 12 weeks, supporting its use as a promising scaffold for repair and resurfacing of articular cartilage defects, in the clinical setting.